The acceptance of food waste innovation products among households in Kuala Lumpur / Nur Nadiah Hafizah Harun and Nurul Ainun Syamimi Azmi - Harun, Nur Nadiah Hafizah; Azmi, Nurul Ainun Syamimi (2021)
Food waste has been a worldwide concern for several decades due to growing evidence that municipal waste generation has increased globally and locally in recent years. Food waste to be recognized as a complex issue that affects the world's sustainable development, including the environment, economy, and society. In 2015, the total food waste had reached approximately 33% in Southeast Asia, including Malaysia. Therefore, the purpose of this paper is to identify the factors that affect food waste innovation products among households and to determine to what extent food waste innovation products can reduce wastage in Malaysia. The quantitative method was applied through online questionnaire survey distributed to respondents that were randomly selected in Kuala Lumpur and total about 213 questionnaires were completed and returned with reliable and meaningful results. The results clearly show that knowledge and behavior positively affect the acceptance of food waste innovation products among households. Besides, it was found that the households in Kuala Lumpur show the positive feedback on the notion of food waste innovation products can be a viable option in reducing food waste in our country.